Evaluating iron deposition in gray matter nuclei of patients with acute ischemic stroke using quantitative susceptibility mapping - Zhou, Li; Yang, Jie; Zhang, Wei; Han, Limei; Zhou, Shenghai; Zheng, Chunyan; Feng, Hao; Zhong, Jianquan (Frontiers in Neurology, 2024)
ObjectivesUnderstanding the microscopic pathophysiological mechanisms underlying acute ischemic stroke (AIS) is vital for facilitating early clinical diagnosis and intervention. In this study, we aimed to quantitatively assess brain iron changes in gray matter (GM) nuclei in patients with AIS via quantitative susceptibility mapping (QSM).MethodsThirty-four patients with AIS and thirty age-and sex-matched healthy controls (HCs) were included. QSM and conventional magnetic resonance imaging were performed. Intergroup differences in regional susceptibility values were calculated for the bilateral caudate nucleus (CN), globus pallidus (GP), putamen (PUT), red nucleus (RN), substantia nigra (SN), thalamus (THA), and dentate nucleus (DN). A receiver operating characteristic curve was plotted to evaluate the classification and diagnostic performance of susceptibility values in distinguishing patients with AIS from HCs. Multiple linear regression analysis was used to investigate the impact of clinical variables on susceptibility values. Correlation analysis was used to assess the correlation between regional iron variations and clinical scores. A paired t test was used to calculate the differences in susceptibility values between the bilateral hemispheres in the participants.ResultsCompared with the HCs, the patients with AIS had significantly increased susceptibility values in the bilateral CN and PUT (p < 0.05, FDR correction). The highest diagnostic performance was observed in the combination of susceptibility values with differences between groups (AUC = 0.722). Multiple linear regression analysis revealed that increased susceptibility in the right CN was significantly associated with smoking (p < 0.05). The susceptibility values were not significantly correlated with the clinical scores (p > 0.05), but age was positively correlated with the modified Rankin Scale scores at admission (p < 0.05). The susceptibility values of the SN exhibited lateral asymmetry in patients with AIS.ConclusionThis study revealed increased iron concentrations in the GM nuclei of patients with AIS. Iron deposition in GM nuclei may be a potential biomarker for further understanding the pathophysiological mechanism underlying AIS.